Passengers' service perceptions emerging from user-generated content during the pandemic: the case of leading low-cost carriers - Saydam, Mehmet Bahri; Olorunsola, Victor Oluwafemi; Rezapouraghdam, Hamed (Emerald Group Publishing Ltd, 2023)
Purpose Although a vast amount of research has been started to gauge customer satisfaction using surveys, the influence of COVID-19 on passengers' satisfaction has not received enough attention. Hence, the primary purpose of this research is to determine the dominant themes that emerged from airline travelers' online reviews and to determine attributes that are pertinent to the satisfaction of passengers flying with low-cost carriers (LCC) during the COVID-19 outbreak. In addition, this study investigates whether the salient themes of passengers' overall experiences vary by traveler origin, which may give more insight into airline sector market segmentation. Design/methodology/approach Leximancer software was used to construct concepts from words, followed by themes in the data analysis. Findings The analyses revealed eight themes in descriptions of travel experiences for airline passengers. These are flights, staff, service, hygiene, cancellations, legroom, COVID-19 and test. Negative reviews associated with cancellations, refund, waiting and baggage (handling) concepts. Originality/value The findings provide important information about airline passengers' overall experiences. Limited studies have comprehensively considered various satisfaction categories of airline travelers using online reviews.
Keywords: Low-cost airlines; Service perception; Satisfaction; Content analysis; Online reviews